Jordanian EFL Students’ Types of Intelligence in Learning English - Ababneh, Sana’ (Journal of Education and e-Learning Research, 2021)
The present study investigated the types of intelligence BAU students prefer to use in learning English. This study used a quantitative method for collecting data via a questionnaire. The subjects of the study were 138 Jordanian students at Al-Huson University College, Al-Balqa Applied University. The results revealed that logical-mathematical and linguistic intelligence was the most dominant type of intelligence among the students. However, neither their gender nor their academic degree program had a significant effect on their learning type of intelligence. Nevertheless, the data showed substantial differences among the students in the interpersonal type of intelligence in favor of male students, while these differences were in favor of the females in the intrapersonal type. There were significant differences in the logical-mathematical type of intelligence between the bachelor’s degree students and their diploma colleagues in favor of the bachelor ones. The researcher attempts to shed light on Jordanian EFL students’ types of intelligence and their preferred types when learning English, in hopes that it becomes possible for teachers to recognize the types according to their students’ profiles and help match them with those present or assess whether they need to develop strategies to cover the full spectrum of the types found in MI Theory.